Increasing credibility in government assignments: an example from Sweden of stakeholder involvement by using Concept Mapping - Frida Smith; Katrín Ásta Gunnarsdóttir; Katarina Fredriksson; Mikael Holtenman; Christina Carlsson (BMJ Open Quality)
Background The incidence of people diagnosed with cancer is increasing worldwide, in Sweden with approximately 65 000 new cases yearly. To enhance conditions for a continued good life, high-quality, accessible and equal cancer rehabilitation is required. In 2020 the National Board of Health and Welfare (NBHW) received a government assignment to investigate the conditions for the offer of cancer rehabilitation. This paper aims to highlight how the Concept Mapping (CM) methodology was strategically used by the NBHW for mutual learning to raise different perspectives and ‘voices’ of cancer rehabilitation.Methods The stepwise, mixed-method CM was used. A broad selection of relevant stakeholders was invited to complete the prompt: a good and equal cancer rehabilitation requires… the stakeholders were involved in brainstorming, sorting and grading data. The research group performed multi-dimensional scaling and hierarchical cluster analysis to provide a visual presentation of the results. Two digital seminars were held: one where stakeholders did online sorting and grading of data and one where results were presented and discussed.Results 118 respondents from four stakeholder groups provided 489 original ideas. Six clusters from 67 unique ideas constituted the concept map, and a go-zone showing the 12 ideas rated as most important and feasible was obtained.Conclusion For the first time, the NBHW has used CM in investigative work to produce development proposals and improvements that the government can use as a basis for political decisions. The method showed great potential, by allowing for stakeholder involvement as co-creators in all steps, high participation and possible direct utilisation of results. A clear learning perspective was obtained, both from the NBHW and the involved stakeholders; hence, the method can be used in further assignments where improvement perspectives are requested.